Manifold-Based Machine Learning for Activity Detection in Grant-Free Massive MIMO Systems - ElSakka, Omar (2026)
A Master of Science thesis in Electrical Engineering by Omar ElSakka entitled, “Manifold-Based Machine Learning for Activity Detection in Grant-Free Massive MIMO Systems”, submitted in April 2026. Thesis advisor is Dr. Mahmoud H. Ismail. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).